(untitled) (International Journal of Medical and Surgical Sciences, 2017)
Advertising has become a critical success factor for companies. In the case of dental products, consumers primarily consider the benefits of the product before purchasing. However, there are other relevant factors in consumer interaction with the dental advertising. The aim of this article is to present the results of research on advertising and its influence on purchasing decisions of products and / or dental services. Several authors have identified factors related to successful ads, some speak about creativity and others give importance to brand management, among others. Dentists found that consumers are generally receptive to the use of advertising. Advertising can be a powerful tool for recruiting future patients and to ensure current patients, but the precepts required by dental ethics code must be respected. It is necessary further research about the implications of advertising in dental services.